Nucleocapsid Protein-Based Enzyme-Linked Immunosorbent Assay for Detection and Differentiation of Antibodies against European and North American Porcine Reproductive and Respiratory Syndrome Virus - Seuberlich, Torsten (American Society for Microbiology, 2002)
Two types of porcine reproductive and respiratory syndrome virus (PRRSV) have been reported, the European type (EU PRRSV) and the North American type (US PRRSV). We developed a dual enzyme-linked immunosorbent assay (ELISA) for the simultaneous detection and differentiation of serum antibodies directed against either of the two PRRSV types. This tandem PRRS ELISA is based on affinity-purified recombinant nucleocapsid protein expressed in Escherichia coli. Sensitivity and specificity were assessed by using the IDEXX HerdChek PRRS ELISA and the indirect immunofluorescence assay as reference tests. A total of 1,571 sera originating from the United States, Europe, and two PRRS-free countries, i.e., Switzerland and New Zealand, were used for validation of the tandem PRRS ELISA. The new test performed at least as well as the reference tests in regard to sensitivity (0.94 for the US PRRS ELISA and 0.93 for the EU PRRS ELISA) and specificity (0.96 for the US PRRS ELISA and 0.99 for the EU PRRS ELISA). Positive sera were correctly differentiated in 582 of 591 cases, indicating a high differentiation capability of this dual ELISA. The robustness and repeatability of the test were assessed and found to be appropriate for diagnostic applications. Taken together, the data indicate that the tandem PRRS ELISA described here is the first differentiation ELISA for PRRSV serology based on recombinant antigen. It is convenient with respect to antigen production, and it is reliable, economical, and highly sensitive and specific. Thus, it is considered to be a powerful tool for routine diagnostics, epidemiological surveys, and outbreak investigations.